PRODUCTIVITY OF KENAF CROP ( Hibiscus cannabinus L.) BY EFFECT MANY PLANTING DATES IN BASRAH GOVERNORATE 2-For seed and oil production - Majid, Hashim (University of Thi-Qar Journal of Science, 2010)
In order to evaluate the productivity of kenaf ( Hibiscus cannabinus L.)for seed and oil production ,this study was conducted during the growing season of year 1998 and 1999 to determine the productivity of three varieties (Vit11,Vso1and the local variety as a control) by effect four planting dates (20February,10March,30March and 20 April) on seed yield ,seed yield components , oil percentage and oil yield. The experiment design in both years was randomized complete block, replicated four times. The treatments were in a split plots arrangement where planting dates constituted the whole plots and varieties the sub plots. Seed yield differences were observed among varieties, planting times and theirinteraction .The local variety (the control)gave the highest seed yield (921.5 g /m ) when planted on 30 March followed by the variety Vso1(696.9 g /m2 )then the variety Vit 11 gave the lowest seed yield (441.4 g /m 2 )when they planted on the same date. Earlier planting dateand later than 30 March reduced the seed yield of all varieties significantly. Seed yield differences among varieties were the consequence of differences in number of capsules/plant and number of seeds/capsule. The results also showed that the low1000 seed weight of the local variety was compensated by the high capsules /plant and seeds / capsule to give higher seed yield. Earlier planting date and later than 30 March reduced yield components especially number of capsules/plant and seeds/capsule and that reflected on seed yield result among planting dates.